Serological diagnosis and prevalence of HIV-1 infection in Russian metropolitan areas - D. E. Kireev; V. P. Chulanov; G. A. Shipulin; A. V. Semenov; E. V. Tivanova; N. M. Kolyasnikova; E. B. Zueva; V. V. Pokrovskiy; C. Galli (BMC Infectious Diseases, 2021)
Abstract Background HIV infection is a major health problem in Russia. We aimed to assess HIV prevalence in different population groups and to compare the characteristics of 4th generation immunoassays from Abbott, Bio-Rad, Vector-Best, Diagnostic Systems, and Medical Biological Unit. Methods The study included 4452 individuals from the general population (GP), 391 subjects at high risk of HIV infection (HR) and 699 with potentially interfering conditions. HIV positivity was confirmed by immunoblot and by HIV RNA, seroconversion and virus diversity panels were also used. HIV avidity was employed to assess recent infections. Results The prevalence in GP was 0.40%, higher in males (0.62%) and in people aged < 40 years (0.58%). Patients attending dermo-venereal centers and drug users had a high prevalence (34.1 and 58.8%). Recent infections were diagnosed in 20% of GP and in 4.2% of HR. Assay sensitivity was 100% except for one false negative (99,54%, MBU). Specificity was 99.58–99.89% overall, but as low as 93.26% on HR (Vector-Best). Small differences on early seroconversion were recorded. Only the Abbott assay detected all samples on the viral diversity panel. Conclusion HIV infection rate in the high-risk groups suggests that awareness and screening campaigns should be enhanced. Fourth generation assays are adequate but performance differences must be considered.